Strategi Pemberdayaan Kesejahteraan Keluarga (PKK) dalam Meningkatkan Ekonomi Keluarga Desa Sipinggan Lumbansiantar, Kecamatan Nainggolan, Kabupaten Samosir - LUMBANSIANTAR, CHRISDAYANTHY; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p06, 2023)
Family Welfare Empowerment Strategy (PKK) in Improving Family Economy Sipinggan Lumbansiantar Village, Nainggolan District, Samosir Regency Family Welfare Empowerment (PKK) is an organization engaged in community development, with 25 members domiciled in Sipinggan Lumbansiantar Village. Its existence is expected to increase the creativity of the community so that it can improve the family’s economy by utilizing the yard they have. The objectives of the study include identifying internal and external factors and developing PKK strategies. Research methods include. (1) interviews with respondents and key informants, (2) analysis of the IFAS and EFAS matrices, (3) formulating strategies with SWOT. The results showed that the internal factor that became the strength was that farming could help the PKK family’s economy in Sipinggan Lumbansiantar Village. The internal factor that becomes a weakness is that the members have less creativity. Meanwhile, the external factor that becomes an opportunity is the availability of tradisional markets as a place to sell the products produced. External factors that pose a threat are the incitement that the PKK is considered a waste of time and people who prefer to buy instant ones rather that using their home yards. The Family Welfare Empowerment Strategy (PKK) in improving the family economy of Sipinggan Lumbansiantar Village was obtained from SWOT.